Research design : qualitative, quantitative, and mixed methods approaches - Creswell, John W.; Creswell, J. David (Los Angeles : SAGE, 2023)
"The new edition of the best-selling text, Research Design: Qualitative, Quantitative, and Mixed Methods Approaches by John W. Creswell and co-author J. David Creswell, continues the pioneering tradition of providing clear and concise instruction for understanding research and developing proposals for all three approaches. This classic text walks students through research methods, starting with a preliminary consideration of philosophical assumptions, continuing with a review of the literature, an assessment of the use of theory in research approaches, and ending with reflections about the importance of writing and ethics in scholarly inquiry in a way that is applicable to all types of research. Coverage of key elements of the research process helps readers organize and develop their research project, giving specific attention to each methodological approach. The book has been lauded for its language and tone, which are both accessible and inviting. Students keep and continue to use this text as a resource throughout their studies, once the specific class is over. The Sixth Edition includes more coverage of community-based participatory research, comparisons of qualitative and quantitative research, an expanded glossary with basic terms, updated examples of social, behavioral, and health research, new coverage of ethical requirements, updated APA 7th edition coverage, and additional exercises aimed at research projects"--
Includes bibliographical references and index.
Texto en inglés.
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Statistical methods